Governor age and fraud in Indonesia: Examining the roles of transparency, accountability, and integrity - Simbolon, Ramadona (Jurnal Akuntansi dan Auditing Indonesia, 2025)
The Indonesian government has launched various policies to prevent fraud by strengthening transparency and integrity. However, fraud in Indonesia remains high, including in regions that experience an increase every year. This study examines the mediating effect of transparency and accountability on the relationship between the age of the governor and fraud, as well as the moderating effect of integrity on the relationship between transparency, accountability, and fraud. This research was conducted in the Provincial Governments in Indonesia. Using the purposive sampling method, the research sample consists of 32 provincial governments in Indonesia during the period 2021-2023, resulting in 96 units of analysis. The data analysis of this research uses multiple regression, mediating regression, and moderating regression. The research results show that the age of the governor does not play a role in reducing fraud but directly contributes to fraud, while integrity does not moderate the influence of transparency and accountability on fraud. Conflict of interest between the executive and legislative branches in provincial government triggers political pressure, potentially leading to collusion that can reduce their oversight and honesty, thereby weakening transparency, accountability, and integrity, and increasing the risk of fraud. The separation of the functions of the Governor and legislators in the province must be implemented in best practices and reinforced in regulations.